Вербализация отрицательных эмоций: архаические и инновационные средства - Слипецкая, Вера (Studia Rossica Posnaniensia, 2014)
The article focuses on the topic of verbalizing negative emotions. It also deals with certain manifestations of a new communicative behavior, the formation of a new Russian language personality that shows inclination for conflict communication style, new speech standards: excessive use of borrowings, vulgarisms, unnatural interjections as well as tonality, and a special manifestation of the so-called “phonetics and grammar of emotions”.